On the influence of cooling rate in heat-treated Cu-Al-Ti-Ta high-temperature shape memory alloys - Yildiz, Koksal (Elsevier Science Sa, 2020)
The effect of cooling rate on microstructural, structural, transformation and shape recovery properties of heat-treated Cu-12.4Al-1.2Ti-1.2Ta (wt.%) alloy has been studied. As cooling rate decreases, the phase components and transformation behavior of the alloy changes dramatically and therewith, the shape recovery ratio of the alloy decreases.
Keywords: Cu-based HTSMA; Cooling rate; Shape memory alloys; Martensite; Shape-memory effect